2020
DOI: 10.1016/j.nmni.2020.100755
|View full text |Cite
|
Sign up to set email alerts
|

Coagulase-negative staphylococci (CoNS) meningitis: a narrative review of the literature from 2000 to 2020

Abstract: Coagulase-negative staphylococci (CoNS) are recognized as comprising the main part of human normal microbiota and are rarely associated with severe and intensive infections. However, these organisms can cause a number of infections in humans, especially immunocompromised patients and neonates. Bacterial meningitis, as an important and acute infection in the central nervous system, is still a major global health challenge and a serious infectious disease, causing a high rate of mortality and morbidity. CoNS as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 80 publications
(107 reference statements)
2
27
0
1
Order By: Relevance
“…We observed that 100% and 95% of the isolates were resistant to benzylpenicillin and oxacillin respectively, this result was also supported by cefoxitin screening, which is widely accepted as a surrogate for the detection methicillin resistance in staphylococci 19 , as well as the detection of mecA gene by PCR in these isolates. Similar results were reported elsewhere 8 , the high prevalence in pinicillins resistance in Staphylococcus haemolyticus is perhaps explained by the high diversity of staphylococcal cassette chromosome mec (SCCmec) element that is carried by Staphylococcus haemolyticus strains 7, 8, 20 , this high diversity of the Staphylococcus haemolyticus SSCmec genes suggest that the bacteria is an important reservoir for the dissemination of these genes among other staphylococci within health care settings 20, 21 .…”
Section: Resultssupporting
confidence: 76%
“…We observed that 100% and 95% of the isolates were resistant to benzylpenicillin and oxacillin respectively, this result was also supported by cefoxitin screening, which is widely accepted as a surrogate for the detection methicillin resistance in staphylococci 19 , as well as the detection of mecA gene by PCR in these isolates. Similar results were reported elsewhere 8 , the high prevalence in pinicillins resistance in Staphylococcus haemolyticus is perhaps explained by the high diversity of staphylococcal cassette chromosome mec (SCCmec) element that is carried by Staphylococcus haemolyticus strains 7, 8, 20 , this high diversity of the Staphylococcus haemolyticus SSCmec genes suggest that the bacteria is an important reservoir for the dissemination of these genes among other staphylococci within health care settings 20, 21 .…”
Section: Resultssupporting
confidence: 76%
“…CoNS, such as S. haemolyticus , may be implicated as nosocomial pathogens in device-related infections and can cause bacteremia in patients with chemotherapy-induced neutropenia [1] . CoNS are an uncommon cause of bacterial meningitis, occurring predominately when there is disruption of protective central nervous system (CNS) structures such as in traumatic brain injury [3] , [4] or craniotomy. CoNS form biofilms and are often implicated in neurosurgical device associated meningitis and ventriculitis [2] .…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, good treatment outcomes have been described with a combination of device removal and intravenous vancomycin (median 12.5 days duration post-device removal) [2] . In patients without a neurosurgical device, and therefore no option for source control, descriptions of treatment are limited to case reports [4] . Successful management of a patient with Staphylococcus epidermidis bacteremia and meningitis on a background of AML, and no history of neurosurgery, was achieved with a 39-day course of intravenous vancomycin and oral rifampin [5] .…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus can cause skin and soft tissue disease, pleuropulmonary disease, medical device-related bloodstream infections, food poisoning, and even infective endocarditis or osteomyelitis ( Lowy, 1998 ; Lindsay and Holden, 2004 ; Tong et al, 2015 ; Kavanagh et al, 2018 ; Lakhundi and Zhang, 2018 ; Oliveira et al, 2018 ; Turner et al, 2019 ; Horino and Hori, 2020 ; Pimentel de Araujo et al, 2021 ). Although less virulent than S. aureus , CoNS including Staphylococcus epidermidis, Staphylococcus haemolyticus, Staphylococcus saprophyticus, Staphylococcus capitis, Staphylococcus lugdunensis, Staphylococcus hominis, Staphylococcus schleiferi , and Staphylococcus warneri are also important staphylococcal pathogen and are usually associated with hospital infections such as skin and soft tissue disease, sepsis, meningitis, endocarditis, and catheter- or implanted device-mediated infections ( Vuong and Otto, 2002 ; Otto, 2009 ; Becker et al, 2014 ; Natsis and Cohen, 2018 ; Azimi et al, 2020 ; Parthasarathy et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%